VISUAL ANTHROPOLOGY: PRIORITY OF ETHICAL PRINCIPLES / ВИЗУАЛЬНАЯ АНТРОПОЛОГИЯ: ПРИОРИТЕТ ЭТИЧЕСКИХ ПРИНЦИПОВ - ALEKSANDROV EVGENY V. / АЛЕКСАНДРОВ Е.В. (Наука телевидения)
The article discusses the features of creating artworks based on the visual anthropology principles. Robert Flaherty, who in 1992 shocked the audience with his film “Nanook of the North” about the life of a smallnumbered people at the end of the world, is the acknowledged pioneer of the new trend of documentary films. With time the anthropologists realized that filming based on “included observation,” the main research method of the Franz Boas cultural relativism school, opens new opportunities for cultural studies. Obtained on-screen content can be used for crosscultural communication based on the authentic information and the ethical principles of equitable “culture dialogue.” In this case the determining principle that differentiates the visual anthropology from other means of communication aims at establishing the “culture dialogue,” when the intermediary moral responsibility before both cultures—those reflecting and receiving the information, comes to the fore. With this approach to studying reality reflection patterns, one may talk about cinethics (cinematography ethics), using this notion to describe the priority of the ethical principles in cinematographic research within the framework of visual anthropology. The principles of moral responsibility determine the work nature of all participants throughout all stages of their activity in the area of visual anthropology. Consequently, a special attention is paid to and a significant amount of text is dedicated to the features of the original work of the cameraman at the initial phase of filming the event.